Unmasking the Primary: The Role of 99mTc-Sestamibi SPECT/CT in a Case of Carcinoma of Unknown Primary with Suspected Lung Origin - Jessica Ubercaprita; Endah Indriani Wahyono; Mas Adi Sunardi; Herry Herman; Bethy Suryawathy Hernowo; Basuki Hidayat (HM Publisher, 2025)
Background: Carcinoma of unknown primary (CUP) is a challenging clinical diagnosis, representing histologically confirmed metastatic cancer where the primary tumor site remains unidentified after a standard diagnostic workup. While 18F-FDG PET/CT is recommended by current guidelines, its accessibility is limited in many regions. This report explores the diagnostic utility of Technetium-99m (99mTc)-Sestamibi Single Photon Emission Computed Tomography/Computed Tomography (SPECT/CT) as a valuable alternative. Case presentation: A 67-year-old female presented with musculoskeletal pain. A biopsy of a right ulnar lesion confirmed metastatic carcinoma. Immunohistochemistry (IHC) suggested a possible primary from the lung, breast, or upper gastrointestinal tract. Due to the unavailability of 18F-FDG PET/CT, a 99mTc-Sestamibi whole-body scan with SPECT/CT was performed. The scan identified a metabolically active, malignant-appearing nodule in segment 6 of the left lung and confirmed widespread skeletal metastases. Although a lung biopsy was not feasible due to limited access, the patient was treated with a lung cancer protocol. This resulted in significant clinical improvement. Conclusion: 99mTc-Sestamibi SPECT/CT served as a critical diagnostic tool in this case of CUP. It successfully identified a suspected pulmonary primary, enabling targeted therapy and leading to a positive clinical outcome. This case highlights the modality's efficacy as a tumor-seeking agent and underscores its essential role in the diagnostic armamentarium for CUP, particularly in resource-limited healthcare settings.